O ritual do batismo em Portugal na Baixa Idade Média e nos inícios do século XVI - Francisca Pires de Almeida (Medievalista)
The ritual of child baptism is still lacking attention in Portuguese historiography. In this article I will focus on its evolution during the Middle Ages, from the moment Saint Augustine of Hippo drew its foundations, until the sixteenth century and the pressure exerted by the Protestant Reformations on the Catholic Church.